TRANSFORMASI MASYARAKAT PETANI MRANGGEN MENUJU MASYARAKAT INDUSTRI - Kuat Ismanto; H. Misbahul Huda; Chusna Maulida (JURNAL PENELITIAN, 2012)
This research is to describe and analyze (1) how the farming community facing industrialization going on in Mranggen, (2) how is the changes of socio-religious values of the farmers, (3) whether the religion is still regarded as public life and private life in the society. The results is that: first, industrialization in Mranggen started since 1995's with the establishment of a wide range of industries. For a farmer, industrialization is a blessing because his land is more expensive and he can go on pilgrimage by selling his land. For the unemployed and women, it is to get job. For the society as a new trader, it is chance to peddle merchandise. For local government, it is as a successful economic development and local revenue. Second, the transformation of society into an industrial society brings about changes in Mranggen: in infrastructure, housing developments, as well as the modernization of agriculture, thus narrowing the field of agricultural workers. Third, the value of new growth in the industrial society, religion still has a hallowed place in public life and private life.